2011
DOI: 10.1590/s1806-37132011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Radiografia torácica e bacteriologia na fase inicial de tratamento de 800 pacientes masculinos com tuberculose pulmonar

Abstract: Objective: To evaluate chest X-rays of patients with pulmonary tuberculosis and to determine whether the extent of radiographic lesions correlates with bacteriological parameters. Methods: In this retrospective, descriptive study, we evaluated chest X-rays, as well as AFB detection by smear microscopy and culture for Mycobacterium tuberculosis, initially and during the first two months of treatment, in 800 male patients hospitalized between 1995 and the present at a 250-bed hospital in northwestern Turkey. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
1
0
3
Order By: Relevance
“…A high proportion of patients in this study had radiological evidence of cavitation (78%), compared with 72% in a study of 800 Turkish patients [ 20 ], 53.1% in a study of 893 USA-based patients [ 48 ], and 51% in a recent multicenter trial of 1692 patients in African sites [ 49 ]. Previous reports have suggested that the presence and number of cavities is related to bacterial load [ 12 , 19 22 , 50 ], but most of these studies were small, with an average of 138 patients (a range of 61–244).…”
Section: Discussionmentioning
confidence: 54%
“…A high proportion of patients in this study had radiological evidence of cavitation (78%), compared with 72% in a study of 800 Turkish patients [ 20 ], 53.1% in a study of 893 USA-based patients [ 48 ], and 51% in a recent multicenter trial of 1692 patients in African sites [ 49 ]. Previous reports have suggested that the presence and number of cavities is related to bacterial load [ 12 , 19 22 , 50 ], but most of these studies were small, with an average of 138 patients (a range of 61–244).…”
Section: Discussionmentioning
confidence: 54%
“…Os dois exames complementares utilizados para diagnóstico e acompanhamento de pacientes com sequela de TB foram à radiografia de tórax e TC, sendo que todos os pacientes realizaram o Raio-X e mais da metade destes (50,6%) a TC. A radiografia de tórax é o método de imagem de escolha na avaliação inicial de pacientes com sequelas de TB, quando o complexo primário da TB evolui para a cura, pode manifestar-se radiologicamente para um nódulo pulmonar ou massa, também chamado de tuberculomas, associado ou não a pequenos nódulos satélites e/ou gânglios mediastinais calcificados 17,18 . Quanto a TC, é um recurso utilizado na suspeita clínica de TB, principalmente nos casos em que a radiografia inicial é normal, esse fato pode justificar o número de pacientes que realizou TC ser inferior ao de pacientes que realizou o Raio-X, visto ser esse último o exame diagnóstico inicial e principal, responsável para o diagnóstico de TB, juntamente com a cultura de escarro 19 .…”
Section: Discussionunclassified
“…Estudos destacam a importância deste exame principalmente em casos de recidivas ou abandono, assim como casos de baciloscopia negativa 24,26 . Embora a baciloscopia e a cultura de escarro sejam indicadas como ferramentas fundamentais para o diagnóstico e acompanhamento de TB pulmonar, nota-se que a radiografia de tórax é mais utilizada no diagnóstico diferencial e avaliação de tratamento da patologia 27 . O PNCT preconiza a utilização desse método para avaliação da doença e de lesões passadas, assim como para definição do tipo e extensão do comprometimento pulmonar 3 .…”
Section: Discussionunclassified